Verification of peroxyacetic acid treatment against L. monocytogenes on fresh apples using E. faecium NRRL B-2354 as a surrogate in commercial spray-bar operations. (December 2020) - Shen, Xiaoye; Su, Yuan; Hua, Zi; Cong, Jian; Dhowlaghar, Nitin; Sun, Qi; Lin, Shengnan; Green, Tonia; Perrault, Mackenzie; Galeni, Marcella; Hanrahan, Ines; Suslow, Trevor V.; et al.
Abstract: Peroxyacetic acid (PAA) is a commonly used antimicrobial in apple spray bar interventions during post-harvest packing. However, limited information is available about its efficacy against foodborne pathogens on fresh apples under commercial packing conditions. In this study, the practical efficacies of PAA against Listeria monocytogenes on fresh apples during spray bar operation at ambient and elevated temperature were validated in three commercial packing facilities using Enterococcus faecium NRRL B-2354 as a surrogate strain. Apples were inoculated with E. faecium at 6.5 Log10 CFU/apple and subjected to PAA spray bar interventions per commercial packing line practice. At each temperature and contact time intervention combination, 20–24 inoculated apples were processed together with 72–80 non-inoculated apples. Applying 80 ppm PAA at ambient temperature (17–21 °C) achieved a similar log reduction ( P > 0.05) of E. faecium on Granny Smith apples (GSA) in three apple packing facilities, which caused 1.12–1.23 and 1.18–1.32 Log10 CFU/apple reductions of E. faecium on GSA for 30-sec and 60-sec intervention, respectively. Increasing the temperature of the PAA solution to 43–45 °C enhanced its bactericidal effect against E. faecium, causing 1.45, 1.86 and 2.19 Log10 CFU/apple reductions in three packing facilities for a 30-sec contact, and 1.50, 2.24, and 2.29 Log10 CFU/apple reductions for a 60-sec contact, respectively. Similar efficacies ( P > 0.05) of PAA at both ambient and elevated temperature were also observed on Fuji apples. Spraying PAA on apples at ambient or elevated temperature reduced the level of E. faecium cross-contamination from inoculated apples to non-inoculated apples but could not eliminate cross-contamination. Data from this study provides valuable technical information and a reference point for the apple industry in controlling L. monocytogenes and verifying the effectiveness of their practices. Highlights: Validate anti- Listeria efficacy of PAA in commercial spray-bar packing lines using E. faecium as a surrogate. A 30-sec of 80 ppm PAA spray wash at 22 °C resulted in 1.0 Log reductions of L. monocytogenes on fresh apples. The enhanced anti- Listeria efficacy of PAA at 43–45 °C were observed in commercial spray-bar packing lines. PAA spray bar interventions reduced but not eliminate L. monocytogenes on fresh apples. The anti- Listeria efficacy of PAA impacted by spray bar alignments.